The CRISPR/Cas Genome-Editing Tool: Application in Improvement of Crops - Khatodia, Surender; Bhatotia, Kirti; Passricha, Nishat; Khurana, S. M. P.; Tuteja, Narendra (Frontiers in Plant Science, 2016)
The Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) associated Cas9/sgRNA system is a novel fledgling targeted genome-editing technique from bacterial immune system, which is a cheap, easy and most rapidly adopted genome editing tool transforming to revolutionary paradigm. Cas9 protein is an RNA guided endonuclease utilized for creating targeted double stranded breaks with only a short RNA sequence to confer recognition of the target in animals and plants. Development of genetically edited (GE) crops similar to those developed by conventional or mutation breeding using this potential technique makes it a promising and extremely versatile tool for providing sustainable productive agriculture for better feeding of rapidly growing population in changing climate. The emerging areas of research for the genome editing in plants are like, interrogating gene function, rewiring the regulatory signaling networks, sgRNA library for high-throughput loss-of-function screening. In this review, we will discuss the broad applicability of the Cas9 nuclease mediated targeted plant genome editing for development of designer crops. The regulatory uncertainty and social acceptance of plant breeding by Cas9 genome editing have also been discussed. The non-GM designer genetically edited plants could prospect climate resilient and sustainable energy agriculture in coming future for maximizing the yield by combating abiotic and biotic stresses with this new innovative plant breeding technique.